The Integration of the Cooperative Integrated Reading and Composition (CIRC) Method in Arabic Language Learning - Laili Mas Ulliyah Hasan; Izzah Nur Hudzriyah Hasan; Muhammad Tareh Aziz (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2025)
This study aims to analyze the effectiveness of integrating the Cooperative Integrated Reading and Composition (CIRC) method in Arabic language learning at the madrasah level. The background of this research is the low reading and writing skills of students, as well as the lack of interaction in the learning process. This study employs both quantitative and qualitative approaches using a classroom action research design. The research sample consists of eighth-grade MTs (Islamic junior high school) students selected through purposive sampling. Data collection techniques include observation, interviews, documentation, and learning achievement tests. Data analysis is conducted using both descriptive quantitative and qualitative methods, along with triangulation to ensure the validity of the findings. The results show that the application of the CIRC method enhances text comprehension, enriches vocabulary, and encourages active student participation through group discussions. The average post-intervention scores increased significantly compared to the initial scores. Thus, the CIRC method is proven to be effective in fostering a more cooperative, communicative, and student-centered Arabic language learning environment.